Two significant historical sources on events in Rogatica and its surrounding in 1941 - Jahić, Adnan (Historical Thought, 2025)
This paper presents the reconstruction of circumstances and events in Rogatica and its surroundings in 1941 on the basis of two sources that have not been used in historical literature devoted to developments in Bosnia and Herzegovina from 1941 to 1945. The author follows the main thread of the narrative of the respective sources, links their notices with the information and statements of other complementary sources and literature and brings a picture of life of a small East-Bosnian city, which, due to its geographical location, ethnic composition of the population, historical heritage and other causes and circumstances, suffered extremely difficult days of fear, destruction, violence and crime in the first year of the Second World War in the occupied Yugoslavia.